Emerging Roles for Pharmacists in Clinical Implementation of Pharmacogenomics. Issue 10 (15th September 2014) - Owusu‐Obeng, Aniwaa; Weitzel, Kristin W.; Hatton, Randy C.; Staley, Benjamin J.; Ashton, Jennifer; Cooper‐Dehoff, Rhonda M.; Johnson, Julie A.
<x xml:space="preserve">Abstract</x> Pharmacists are uniquely qualified to play essential roles in the clinical implementation of pharmacogenomics. However, specific responsibilities and resources needed for these roles have not been defined. We describe roles for pharmacists that emerged in the clinical implementation of genotype‐guided clopidogrel therapy in the University of Florida Health Personalized Medicine Program, summarize preliminary program results, and discuss education, training, and resources needed to support such programs. Planning for University of Florida Health Personalized Medicine Program began in summer 2011 under leadership of a pharmacist, with clinical launch in June 2012 of a clopidogrel‐CYP2C19 pilot project aimed at tailoring antiplatelet therapies for patients undergoing percutaneous coronary intervention and stent placement. More than 1000 patients were genotyped in the pilot project in year 1. Essential pharmacist roles and responsibilities that developed and/or emerged required expertise in pharmacy informatics (development of clinical decision support in the electronic medical record), medication safety, medication‐use policies and processes, development of group and individual educational strategies, literature analysis, drug information, database management, patient care in targeted areas, logistical issues in genetic testing and follow‐up, research and ethical issues, and clinical precepting. In the first 2 years of the program (1 year planning and 1 year postimplementation), a total of 14 different pharmacists were directly and indirectly involved, with effort levels ranging from a few hours per month, to 25–30% effort for the director and associate director, to nearly full‐time for residents. Clinical pharmacists are well positioned to implement clinical pharmacogenomics programs, with expertise in pharmacokinetics, pharmacogenomics, informatics, and patient care. Education, training, and practice‐based resources are needed to support these roles and to facilitate the development of financially sustainable pharmacist‐led clinical pharmacogenomics practice models.